The Effect of Chilbirth Gymnastic Towards Physiological Change on Post-Partum Mother Day I-III in Balikpapan Maternity Clinic - Sonya Yulia; Nina Mardiana (Humanistic Network for Science and Technology (HNST), 2018)
Maternal Mortality Rate in the world is more than one millions every year; the most significant maternal mortality on childbirth of 49.125% and 50% occurs in the first 24 hours. It can be prevented through childbirth gymnastic because it can help accelerating the physiological change like uterine involution, lochea, defecation, and urination, and breast milk production. This research aims to comprehend the effect of childbirth gymnastic towards post-partum maternal physiological change day I-III. This experimental research used randomized two group design. Samples were selected by purposive sampling (30 for experiment group and 30 for control group). The research instruments were observation check list and interview guide. Data were presented in the form of mean, mode and standard deviation, then analyzed by using independent sample t-test. There was an effect of childbirth gymnastic on uterine involution (p-value 0.000); there was an effect of childbirth gymnastic on lochea change (p-value 0.000); there was childbirth change on defecation change (p-value 0.000) and there was an effect of childbirth gymnastic on breast milk production (p-value 0.000). Keywords: Childbirth gymnastic, Physiological change